PENANAMAN NILAI KARAKTER MELALUIPENGEMBANGAN BUDAYA SEKOLAH - Moh. Zainal Fanani (Al Hikmah: Jurnal Studi Keislaman, 2014)
Today, Indonesia government through Education and Culture Ministry tries hard to achieve the cuccess of nation character education. The government has published National Rule of Nation Character Building 2010-2025, and the chief Design of Character Education 2010.The two foundation are used to develop culture and character education in school, and the implementation are through three ways: (1) Namely of self developmentprogram, (2)The integration in courses, and (3) School culture. This article discusses abaut how to build a good character through the development of school culture using some strategies: school routine activity, spontaneous activity, modeling, theaching, and reinforcing of school environment. School culture in the character building must be continuously built and done by the whole school stake holders; start from headmaster, teachers, officers, students, parents, society, and government. Without good school culture, it is difficult to apply character education for students.